P11.14 Pharyngeal and anogenital chlamydia in men who have sex with men: temporal trends and characteristics among attendees at a sydney metropolitan sexual health clinic 2011–2014. (13th September 2015) - Goddard, SL; Rajagopal, P; Templeton, DJ
Abstract : Introduction: Australian STI testing guidelines recommend regular Chlamydia trachomatis (CT) testing at pharyngeal and anogenital sites among asymptomatic men who have sex with men (MSM). Our aim was to investigate temporal trends and characteristics of clinic-diagnosed pharyngeal and anogenital CT among MSM. Methods: Testing was performed using Aptima Combo 2 (Hologic, US). Data were extracted from the laboratory database and medical records. Statistical analyses were performed using STATA13 (Statcorp, College Station, TX). Results: During the study period 2919 MSM were tested on 6850 occasions, and 556 (8.2%) episodes of CT were diagnosed. Pharyngeal (PCT), urethral (UCT) and rectal (RCT) positivity rates were 1.2%, 2.3% and 6.2%, respectively. From 2011–2014, there was a significant increase in number of tests performed, (999–2834, p-trend <0.001), although the positivity rate over the study period remained stable at all 3 sites. There was a non-significant decline in the proportion of those diagnosed with CT who reported any anogenital symptom during the study period (OR 0.85, p-trend = 0.079). Local symptoms were present in 24.3% and 8.0% of those with UCT and RCT, respectively. Of 85 visits where PCT was detected, almost half (n = 39, 45.9%) had no concurrent anogenital infection. Of those, 2 were CT contacts and were treated at the initial visit. Men with PCT had a median of 15 sexual partners over the past year (range1–1000) which was non-significantly higher than men diagnosed with either UCT (p = 0.077) or RCT (p = 0.094). Conclusion: CT positivity remained stable despite substantially increased testing. The temporal decline in symptomatic infections likely reflects a recent policy shift towards regular asymptomatic testing for MSM. Despite a relatively low prevalence of PCT, men with PCT had more sexual partners than men with anogenital CT and close to half the pharyngeal infections would have remained untreated without pharyngeal testing. There may be valuable public health benefits of regular PCT testing among MSM. Disclosure of interest statement: No disclosures of interest.